Obligacje przychodowe - niewykorzystany instrument dłużny - Kozuń-Cieślak, Grażyna (Revenue Bonds - Unused Financial Instruments In Poland, 2006)
Within the confines of the paper: - the essence and attributes of revenue bonds were shown - discussed in the light of legal adjustments, - the barriers of revenue bonds market development were identified, - the main information about and conditions of the first revenue bonds issue in Poland were shown (water supply and sewage system company in Bydgoszcz).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 487-494